LOUCURA, ESCRAVIDÃO E NEGRITUDE - Jorge Álvarez Yágüez (Eleuthería - Revista do Mestrado Profissional em Filosofia da UFMS, 2024)
The Modern Subject is constituted in front of an Other, of which figures such as Madness, Slavery and Negritude are part. The principle of separability, a central part of the modern onto-episteme according to Ferreira da Silva's approach, is central to this constitution. But separability is distancing and imbrication, as is intended to be shown here. The attributes that distinguish Madness, Slavery and Negritude are at the same time associated. And the Modern Subject constituted in front of them, will finally refer to them as its Truth